A Review Paper on various control techniques for Induction Motor Drives - Marulasiddappa H B, Dr.Pushparajesh Viswanathan (International Journal of Advanced Science and Technology, 2020)
This paper introduces the state of art of recent development in control algorithms for Induction motor drives for both industrial and home applications. In present days controlling methods for Induction motor drives plays a pivotal role in order to improve the performance and reducing the torque and flux ripples. Induction motors are normally called constant speed motors. In Industries mechanical loads driven at desired speed. Therefore, the necessity of speed control methods for induction motor comes. There are many techniques of speed control for induction Motor drives. Basically there are two control strategies for induction motor drive system, they are scalar and vector control methods. The limitation of scalar controlling technique like inaccuracy and poor response are overcome by vector control techniques. With advancement in power electronic devices and control techniques, accuracy of the outcome is more. Lot of research is still in progress with respect to minimize the torque ripple and flux ripples in the induction motor drives. Induction motor is a nonlinear machine, modelling is very difficult due to sudden variation of load. Hence it is necessary to design variable speed drives (VSD) to improve dynamic performance. An improved control techniques are necessary to design for controlling voltage, torque, flux and reducing total harmonic distortion (THD). Implement of these controlling methods needs big mathematical models and require high computational complexity. The use of different control technique is based on the type of applications. To incorporate this, many control strategies are built for induction motor drives for different industrial and home applications. This paper reviews on different algorithms involved in controlling of induction motor drives. Keywords–Induction motor drive, direct torque control, control methods, intelligent controllers